Perinatal Food Deprivation Modifies the Caloric Restriction Response in Adult Mice Through Sirt1 - Peña-Villalobos, Isaac; Otárola, Fabiola A.; Casas, Bárbara S.; Sabat, Pablo; Palma, Verónica (Frontiers in Physiology, 2021)
Variations in the availability of nutritional resources in animals can trigger reversible adjustments, which in the short term are manifested as behavioral and physiological changes. Several of these responses are mediated by Sirt1, which acts as an energy status sensor governing a global genetic program to cope with changes in nutritional status. Growing evidence suggests a key role of the response of the perinatal environment to caloric restriction in the setup of physiological responses in adulthood. The existence of adaptive predictive responses has been proposed, which suggests that early nutrition could establish metabolic capacities suitable for future food-scarce environments. We evaluated how perinatal food deprivation and maternal gestational weight gain impact the transcriptional, physiological, and behavioral responses in mice, when acclimated to caloric restriction in adulthood. Our results show a strong predictive capacity of maternal weight and gestational weight gain, in the expression of Sirt1 and its downstream targets in the brain and liver, mitochondrial enzymatic activity in skeletal muscle, and exploratory behavior in offspring. We also observed differential responses of both lactation and gestational food restriction on gene expression, thermogenesis, organ masses, and behavior, in response to adult caloric restriction. We conclude that the early nutritional state could determine the magnitude of responses to food scarcity later in adulthood, mediated by the pivotal metabolic sensor Sirt1. Our results suggest that maternal gestational weight gain could be an important life history trait and could be used to predict features that improve the invasive capacity or adjustment to seasonal food scarcity of the offspring.